2005
DOI: 10.1128/cdli.12.10.1246-1250.2005
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immunity in Children withMycoplasma pneumoniaeInfection: a 1-Year Prospective Study

Abstract: To determine whether children have persistent abnormalities in cellular and humoral immunity development after acute Mycoplasma pneumoniae infection, serum immunoglobulin G (IgG), IgA, IgM, and IgE levels and lymphocyte phenotypes were determined. There were no changes in the levels of IgG, IgM, IgA, or CD4 ؉ or CD19؉ lymphocytes that were measured in M. pneumoniae-positive patients after 3 months or after 12 months, but there were increases in these in M. pneumoniae-negative patients. Serum IgE increased in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Although no significant difference in immunity status existed between the patients infected with the two pathogens, some studies showed a depressed humoral and cellular immunity in children with M . pneumoniae infection compared to healthy children [30,31]. Because of the difficulty in distinguishing M .…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant difference in immunity status existed between the patients infected with the two pathogens, some studies showed a depressed humoral and cellular immunity in children with M . pneumoniae infection compared to healthy children [30,31]. Because of the difficulty in distinguishing M .…”
Section: Discussionmentioning
confidence: 99%
“…Induction of transient anergy has also been described during the acute phase of Mycoplasma infection [43]. Similarly, a study in children acutely infected by M. pneumoniae reported a temporary suppression of the immune system by mechanisms as yet unknown [44].…”
Section: Pathogenesismentioning
confidence: 97%
“…M. pneumoniae infection was found to increase the production of interleukin-4 (IL-4) and interferon gamma (IfNγ), indicating a predominant Th2-like cytokine response and creating favorable condition for Ige production [12]. Stelmach et al [13] have shown serum Ige increase in children after acute infection with M. pneumoniae. furthermore, lipoproteins and glycoproteins present in the cell membrane and cytoplasm of M. pneumoniae are potent inducers of cytokines that through their molecular mimicry can elicit autoimmunity.…”
mentioning
confidence: 99%